Not Worth the Net Worth? The Democratic Dilemmas of Privileged Access to Information - Guri Rosén; Anne Elizabeth Stie (Politics and Governance, 2017)
In this article, we discuss the democratic conditions for parliamentary oversight in EU foreign affairs. Our point of departure is two Interinstitutional Agreements (IIAs) between the Council and the European Parliament (EP), which provide the latter with access to sensitive documents. To shed light on this issue, we ask to what extent these contribute to the democratic accountability in EU foreign policy? It is argued that the IIAs have strengthened the EP’s role in EU foreign affairs by giving it access to information to which it was previously denied. This does not mean, however, that this increase in power equals a strengthening of the EP as a democratic accountability forum. First of all, both IIAs (even if there are differences between them) fail to maximise the likelihood that the plurality of views in the EP as a whole is reproduced. Secondly, and more importantly, the EU citizens are largely deprived of opportunities to appraise how their elected representatives have exercised their role as guardians of executive power.